Surface science : foundations of catalysis and nanoscience - Kolasinski, Kurt W. (John Wiley & Sons, Inc., 2020)
"The tale of John Yates pushing a copy of Robert and McKee's Chemistry of the Metal-Gas Interface into my hands recedes from the Introduction to the Preface. JTY has passed but his legacy lives on. While Dick Zare was my Dokotorvater, John was my scientific father with some of the ups and downs that accompany meeting someone when you are still an ignorant head-strong kid. This is a time to reflect on how fortunate I was to be able to meet all the luminaries of surface science who paraded through the lab. To recall how I very earnestly explained the infrared reflection absorption spectrum of the rhodium gem dicarbonyl species to an interested listener at the Surface Science Center dedication ceremony. Only to be told afterward that that interested (and very polite) listener was Bob Eischens, who helped invent the field. What a privilege it was to work with, among others, Tom Beebe, Mark Alvey, Ferenc Bozso, John Russell, John Crowell, Jingguan Chen, Kevin Uram, Pat Taylor, and Mike Trenary"-- Provided by publisher.
Keywords: Surface chemistry.; Surfaces (Physics); Catalysis.; Nanoscience.; elektronické knihy; electronic books